Perempuan Sebagai Pelaku Kekerasan dalam Rumah Tangga - Soselisa, Fabio Alexsandro; Toule, Elsa Rina Maya; Tuhumury, Carolina (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Domestic Violence is a crime that has been happening globally for a long time and usually the perpetrators are men, but women can become perpetrators of Domestic Violence because women are one of the spheres of the household.Purposes of the Research: To be able to find out how the accountability of women as perpetrators in criminal acts of domestic violence. Methods of the Research: The method used is a normative research method with a statute, conceptual, and case approach.Results of the Research: In responsibility for the crime, there are processes or stages that must be carried out by perpetrators of domestic violence, starting from the police, the prosecutor's office, and in court. in handling criminal cases, for female perpetrators, the Supreme Court issues Perma No. 3 of 2017 concerning Guidelines for Adjudicating Cases of Women Against the Law, which in this Perma focuses on women as victims, women as witnesses and, women as perpetrators of criminal acts, and in sentencing the sentence usually depends on the judge's decision in accordance with legal facts and laws, or regulations.